Community security - the irish problem - Gardiner, Frances K. (Economic & Social Studies, 1986)
Consideration of some theoretical literature on community involvement in crime control is useful in clarifying the ultimate objectives of such schemes. Characteristic of crime in Ireland is the high incidence of offences against property rather than against the person, together with the failure of the Criminal Justice System to address them effectively. It is argued here that while modern society lacks the bonding of traditional solidarity, it nevertheless possesses a reciprocal-associational solidarity that could lend itself to a communal approach to crime control. The mutual aim of avoidance of economic loss may account for the motivational factor.
Keywords: Crime - Ireland; Criminal Justice System - Ireland